Double zero-tillage and foliar-P nutrition coupled with bio-inoculants enhance physiological photosynthetic characteristics and resilience to nutritional and environmental stresses in maize–wheat rotation - M. N. Harish; M. N. Harish; Anil K. Choudhary; Anil K. Choudhary; Ingudam Bhupenchandra; Anchal Dass; G. A. Rajanna; G. A. Rajanna; Vinod K. Singh; Vinod K. Singh; R. S. Bana; T. Varatharajan; et al. (Frontiers in Plant Science, 2022)
Conventionally tilled maize–wheat cropping system (MWCS) is an emerging cereal production system in semi-arid region of south-Asia. This system involves excessive tillage operations that result in numerous resource- and production-vulnerabilities besides impeding environmental-stresses. Likewise, phosphorus is a vital nutrient that limits crop growth and development. It’s a matter of great concern when ∼80% of Indian soils are low to medium in available-P due to its sparing solubility, resulting in crop stress and low yields. Hence, crop productivity, photosynthetic parameters and resilience to nutritional and environmental stresses were assessed in a MWCS using four crop-establishment and tillage management (CETM) practices [FBCT-FBCT (Flat bed-conventional tillage both in maize and wheat); RBCT-RBZT (Raised bed-CT in maize and raised bed-zero tillage in wheat); FBZT-FBZT (FBZT both in maize and wheat); PRBZT-PRBZT (Permanent raised bed-ZT both in maize and wheat)], and five P-fertilization practices [P100 (100% soil applied-P); P50+2FSP (50% soil applied-P + 2 foliar-sprays of P through 2% DAP both in maize and wheat); P50+PSB+AM-fungi; P50+PSB+AMF+2FSP; and P0 (100% NK with no-P)] in split-plot design replicated-thrice. The results indicated that double zero-tilled PRBZT–PRBZT system significantly enhanced the grain yield (6.1; 5.4 t ha–1), net photosynthetic rate (Pn) (41.68; 23.33 μ mol CO2 m–2 s–1), stomatal conductance (SC) (0.44; 0.26 mol H2O m–2 s–1), relative water content (RWC) (83.3; 77.8%), and radiation-use efficiency (RUE) (2.9; 2.36 g MJ–1) by 12.8–15.8 and 8.5–44.4% in maize and wheat crops, respectively over conventional tilled FBCT–FBCT. P50+PSB+AMF+2FSP conjugating soil applied-P, microbial-inoculants and foliar-P, had significantly higher Pn, SC, RUE and RWC over P100 besides saving ∼34.7% fertilizer-P under MWCS. P50+PSB+AMF+2FSP practice also had higher NDVI, PAR, transpiration efficiency and PHI over P100. Whereas lower stomatal limitation index (Ls) was observed under PRBZT–PRBZT system as compared to the conventional FBCT–FBCT system indicating that P is the limiting factor but not stomata. Hence, optimum P supply through foliar P-fertilization along with other sources resulted in higher grain yield by 21.4% over control. Overall, double zero-tilled PRBZT–PRBZT with crop residue retention at 6 t/ha per year, as well as P50+PSB+AMF+2FSP in MWCS, may prove beneficial in enhancing the crop productivity and, thereby, bolstering food security in semi-arid south-Asia region.